2014
DOI: 10.1128/jvi.03805-13
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions near the Hemagglutinin Receptor-Binding Site Determine the Antigenic Evolution of Influenza A H3N2 Viruses in U.S. Swine

Abstract: Swine influenza A virus is an endemic and economically important pathogen in pigs, with the potential to infect other host species. The hemagglutinin (HA) protein is the primary target of protective immune responses and the major component in swine influenza A vaccines. However, as a result of antigenic drift, vaccine strains must be regularly updated to reflect currently circulating strains. Characterizing the cross-reactivity between strains in pigs and seasonal influenza virus strains in humans is also impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 49 publications
2
122
0
Order By: Relevance
“…The amino acid residues identified in the present study as critical for the antigenic difference between A(H3N2)v and seasonal H3N2 viruses are all located near the RBS in HA, which is in agreement with the observations in other studies that examined H3N2 antigenic evolution (19,23,24). Our study indicated that the amino acid mutations which switched the antigenic phenotype of MN/10 and BJ/92 influenced receptor binding.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The amino acid residues identified in the present study as critical for the antigenic difference between A(H3N2)v and seasonal H3N2 viruses are all located near the RBS in HA, which is in agreement with the observations in other studies that examined H3N2 antigenic evolution (19,23,24). Our study indicated that the amino acid mutations which switched the antigenic phenotype of MN/10 and BJ/92 influenced receptor binding.…”
Section: Discussionsupporting
confidence: 82%
“…A(H3N2)v isolates are antigenically distinct from recent human seasonal H3N2 viruses as well as H3N2 viruses that circulated in humans during the period when they are thought to have been introduced into swine (2,3,19). Although amino acids close to the receptor binding site (RBS) in hemagglutinin (HA) are associated with antigenic evolution of human seasonal H3N2 and swine H3N2 viruses (23,24), the specific residues that explain why swine-origin A(H3N2)v viruses are antigenically distinct from the human strains have not been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two-way HI assays against a reference swine antiserum panel (see Table S3 in the supplemental material) were performed as described above, using a panel of reference swine and human H3N2 viruses, including Sw/MO/12, Sw/MO/14, and A/VIC/11, as HI antigens (28). The reference panel represents H3 viruses historically or currently circulating in pigs in the United States, along with recent and historical representatives of human vaccine strains.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study did show that contemporary human seasonal H3N2 viruses had obtained substantial antigenic distance from swine H3N2 viruses, even though the lineages shared a common ancestor. Hence, the authors speculated that this increasing distance could pose a risk for the youngest of the human population, as they could become increasingly susceptible to infections with swine H3N2 due to the lack of cross-reacting immunity (Lewis et al, 2014). These findings stress the need for a continued and systematic surveillance of European swine influenza viruses in order to detect new reassortants, as well as monitoring the evolution and zoonotic potential of both reassortant and enzootic swine influenza virus strains.…”
Section: Na Kinetics and Antiviral Susceptibilitymentioning
confidence: 96%